Spiritual healing with children with special needs - Woodward, Bob (Special education teacher) (Jessica Kingsley Publishers, 2007)
Spiritual Healing with Children with Special Needs gives a fascinating account of individual healing sessions with children with complex special needs and moderate to severe learning difficulties. Drawing on his experience as a qualified spiritual healer and senior co-worker at The Sheiling School, a Camphill Centre, Bob Woodward shows how spiritual healing can help children with special needs to achieve peace and relaxation. From his perspective as both spiritual healer and curative educator, the author introduces the key concepts of both subject areas to the reader and explains how the two d.